Does active learning method for higher education promote students’ learning? (Students-teachers perceptions towards the implementation of active learning method) - Kusumaningrum, Widya Ratna; Asmara, Rangga ((JELE) Journal Of English Language and Education, 2019)
Active learning method (ALM) has drawn global attention over the past years. In some Indonesian higher educational institutions, the notion of active learning has changed the university lecturer's perspective. It has flipped it from the conventional tradition to the new idea. This paper aims to study the university lecturer and students’ perception on the implementation of active learning in higher education. This study investigates the university teachers and students perception towards the implementation of ALM to promote the students' learning. The participants of the study were 10 university lecturers and 60 students experiencing and practicing the application of ALM in the second language classroom. The issue was investigated using descriptive qualitative research with close-ended questionnaires. The results showed varied perception, beliefs, and practices on how ALM encouraged collaboration and boosted students’ language performance.